Peningkatan Mutu dan Pendapatan Pengolah Ikan Cakalang Asap di Desa Pontoh, Kecamatan Wori, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara - Pandey, Engel; Pongoh, Jenki (Media Teknologi Hasil Perikanan, 2020)
A low level of sanitation and hygiene applied by smoked fish processors in North Sulawesi can affect the quality and safety of the product itself. Interestingly, there is a huge market demand of smoked fish product in North Sulawesi. That is why Â it is necessary to improve quality of smoked fish product by assisting the smoked fish processors. The program's target partners are located in Pontoh Village, Wori District, North Minahasa Regency which is geographically located on the coast Pontoh Village is categorized as a fishing community, which is about 50% classified as poor families and has a small business group of processing smoked fish. The aim of this program is to increase production, marketing and finance for small entrepreneurs in Pontoh Village, Wori District, North Minahasa Regency so they can be skilled and economically independent. The specific target of this activity is to produce smoked fish products that are superior in terms of taste and shelf life while providing business continuity and strong management. The method of implementation that will be applied to this program are 1) Training on how to produced smoked-fish product using good manufacturing practices Â 2) Assiting about sanitation and hygiene in every step of producing smoked fish; 3) Advising on management